Political Inclusiveness Degree of State Civil Apparatus and Bureaucracy on Mayor and Deputy Mayor Elections in Palu City 2015 - Patta, Abdul Kadir; Basir, Muhammad; Darwis, Darwis; Rivai, Abdul (Devotion : Journal of Research and Community Service, 2023)
This research is based on the condition of the phenomena of the state civil apparatus and the bureaucracy in the election of the mayor and deputy mayor of Palu which is marked by the political events that occur. Simultaneous regional head elections in the province of Central Sulawesi. The theory used is the participation theory from Michael Rush and Philips Althoff and the bureaucratic theory from Max Weber. The aims to analyze how the participation of the community participates in the implementation of the Mayor and Deputy Mayor Elections in 2015. The research method used is descriptive qualitative. Informants were obtained in a purposive way with the criteria of state civil servants, bureaucracy, totaling 7 informants. The results showed that the degree of political inclusivity of state apparatus in the 2015 mayoral and deputy mayoral elections was as follows: state apparatus in the election of the mayor and deputy mayor of Palu were in a neutral position, However, there are several realities where there are emotional and work relationships that are always under pressure, either directly or indirectly, making it difficult to make political decisions individually and have to be involved in the state apparatus situation itself. The Palu city government bureaucracy, which is inclusive in political decision-making, is marked by intrigue from the mayor and deputy mayor officials because based on the law, they hold power over the SKPD, which should be held by the city secretary.